The Relationship between English Language Proficiency and Logical Thinking Skills - Tedjo, Ester Widawati; Hartani, Tuti (Universitas PGRI Semarang, 2022)
The present study investigates the relationship between students’ English language proficiency and their logical reasoning reflected by their performance in applying spreadsheet program. Since logical thinking is the basis of both using English language for communication and operating Microsoft Excel program, students can very likely show similar success in their performance while learning these two skills. The subjects were 67 students enrolled at a secretarial college in Surabaya, Indonesia. Data were collected from the students scores of TOEIC international test and Computer II course focusing on Microsoft Excel. Means of the scores were calculated and the sets of data were analyzed to see if there was a significant correlation between them. The results showed that the students’ English proficiency correlated significantly with their academic performance in computer. It can then be concluded that students with better logical thinking ability seem to be more successful in learning English as a foreign language.